Molecular mechanisms of flavonoid accumulation in germinating common bean (Phaseolus vulgaris) under salt stress - Zhang, Qi; Zheng, Guangyue; Wang, Qi; Zhu, Jixing; Zhou, Zhiheng; Zhou, Wenshuo; Xu, Junjie; Sun, Haoyue; Zhong, Jingwen; Gu, Yanhua; Yin, Zhengong; Du, Yan-li; et al. (Frontiers in Nutrition, 2022)
Flavonoids are important secondary metabolites, active biomolecules in germinating beans, and have prominent applications in food and medicine due to their antioxidant effects. Rutin is a plant flavonoid with a wide biological activity range. Here, flavonoids (rutin) accumulation and its related molecular mechanisms in germinating common bean (Phaseolus vulgaris) were studied at different time points (0h to 120h) under salt stress (NaCl). The rutin content increased from germination onset until 96h, after which a reducing trend was observed. Metabolome analysis showed that salt stress alters flavonoids content by regulating phenylpropanoid (ko00940) and flavonoid (ko00941) biosynthesis pathways, as well as their enzyme activities, including cinnamyl-alcohol dehydrogenase (CAD), peroxidase (POD), chalcone isomerase (CHI), and flavonol synthase (FLS). The RNA-Seq and quantitative real-time PCR (qRT-PCR) analyses also showed that these two pathways were linked to changes in flavonoids content following salt treatment. These results reveal that salt stress effectively enhanced rutin content accumulation in germinating beans, hence could be employed to enhance the functional quality of germinating common beans.